2022
DOI: 10.3390/foods11101403
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Extruded Brewer’s Spent Grain as a Food Ingredient for a Healthy, Safe, and Sustainable Human Diet

Abstract: This study aimed to determine the effect of the extrusion process on the nutritional and bioactive profiles of brewer’s spent grain (BSG), contributing to nutrition security by applying a circular economy concept. Response surface methodology was used to optimize the effect extrusion parameters (moisture content, screw speed, and barrel temperature ) had on BSG’s soluble dietary fiber, free glucose, and overall antioxidant capacity. Proximate composition analyses, amino acid profile, extractable polyphenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Consequently, alkaline extraction of micronised BSG may generate protein isolates rich in glutamate, proline and aspartate but may not be an ideal source of methionine. Moreover, the amino acid composition reported here is consistent with the previous studies presented in Table 1 (Gmoser et al, 2020; Gutiérrez‐Barrutia et al, 2022; Oluseyi et al, 2011; Waters et al, 2012; Yu et al, 2020). Due to its thermal instability, tryptophan is susceptible to breakdown when exposed to high temperatures (Cuq et al, 1983) and therefore lost in the hydrolysis conditions used for amino acid analysis.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consequently, alkaline extraction of micronised BSG may generate protein isolates rich in glutamate, proline and aspartate but may not be an ideal source of methionine. Moreover, the amino acid composition reported here is consistent with the previous studies presented in Table 1 (Gmoser et al, 2020; Gutiérrez‐Barrutia et al, 2022; Oluseyi et al, 2011; Waters et al, 2012; Yu et al, 2020). Due to its thermal instability, tryptophan is susceptible to breakdown when exposed to high temperatures (Cuq et al, 1983) and therefore lost in the hydrolysis conditions used for amino acid analysis.…”
Section: Resultssupporting
confidence: 92%
“… Amino acid composition of BSG from previous studies, presented as a range of the values reported by Gmoser et al (2020), Gutiérrez‐Barrutia et al (2022), Oluseyi et al (2011), Waters et al (2012) and Yu et al (2020). …”
Section: Resultsmentioning
confidence: 99%
“…BSG was utilized as an ingredient during extrusion processing to produce puffed snacks, pasta, breakfast cereals, different nutritional ingredients, and bread [ 8 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Techno-functional Propertiesmentioning
confidence: 99%
“…The extrusion process can improve the balance between soluble and insoluble dietary fiber contents, breaking polysaccharide bonds under mechanical stress, and releasing the content of phenolic compounds trapped in the dietary fibers through shearing. Among the undesirable aspects of extrusion is the Maillard reaction, which favors the production of acrylamide or the reduction in the content of essential amino acids; aspects that depend on the required processing conditions [ 100 ]. Gutiérrez-Barrutia et al studied the effect of extrusion on spent grain and found that extrusion had positive effects on spent grain, increasing the content of soluble dietary fibers, changes caused by the thermo mechanical process that can disrupt the cell wall matrix resulting in smaller and more soluble fragments.…”
Section: Possible Uses Of Spent Grain In Food Productsmentioning
confidence: 99%
“…Gutiérrez-Barrutia et al studied the effect of extrusion on spent grain and found that extrusion had positive effects on spent grain, increasing the content of soluble dietary fibers, changes caused by the thermo mechanical process that can disrupt the cell wall matrix resulting in smaller and more soluble fragments. Extruded spent grain can be considered a suitable ingredient for human consumption from a microbiological point of view [ 100 ].…”
Section: Possible Uses Of Spent Grain In Food Productsmentioning
confidence: 99%